Beta endorphin levels during heroin, methadone, buprenorphine, and naloxone challenges: Preliminary findings - Kosten, Thomas R.; Morgan, Charles; Kreek, Mary-Jeanne (Biological psychiatry (1969), 1992)
Beta endorphin (BE) is a polypeptide agonist for the brain's endogenous opioid system. Levels of BE are elevated by opioid antagonists such as naloxone and depressed by short-acting agonists such as heroin and morphine; they become normalized during steady-state methadone. Buprenorphine (BUP) is a partial opioid agonist whose effects on BE levels were examined in six former heroin addicts and 14 methadone-maintained patients before and after being switched to sublingual BUP 2 mg daily for 1 month. In six former methadone-treated subjects BE levels also were measured after stopping BUP and after naloxone challenge. Levels of BE were not significantly lower in subjects started on BUP after stopping heroin (n = 6) (8.0 versus 8.1 ng/ml) or in subjects started on BUP after stopping methadone (n = 14) (11.6 vs 15.6 ng/ml). However, BE levels were lower on BUP than after naloxone challenge (n = 6) (7.0 versus 34.9 ng/ml). Levels of BE did not significantly change between the first 2 weeks (“early”) and “later,” although BE levels on methadone significantly correlated with BE levels on BUP in the “early” but not the “later” phase. The BE levels on BUP also did not differ from BE levels of unmedicated normals.